Multidimensional perfectionism and assortative mating: A perfect date?. (November 2015) - Hoffmann, Adrian; Stoeber, Joachim; Musch, Jochen
Abstract: Assortative mating has been found regarding personality traits, personal attitudes and values, and cognitive abilities, but so far no study has investigated assortative mating regarding multidimensional perfectionism. A total of 422 participants from a non-commercial panel (mean age = 36.0 years) completed measures of self-oriented, other-oriented, and socially prescribed perfectionism and rated the attractiveness of four potential dating partners ("dates"): a self-oriented, an other-oriented, a socially prescribed, and a non-perfectionist date. Results showed that all perfectionist dates were seen as less attractive than the non-perfectionist date. This effect, however, was moderated by self-oriented and other-oriented perfectionism. Participants high in self-oriented perfectionism found all three perfectionist dates more attractive than participants low in self-oriented perfections. Participants high in other-oriented perfectionism found the self-oriented perfectionist date more attractive, and the non-perfectionist date less attractive than participants low in other-oriented perfectionism. The findings are discussed with respect to assortative mating, the social disconnection model of perfectionism, and the heritability of perfectionism. Highlights: We examined assortative mating regarding multidimensional perfectionism. 422 participants completed measures of multidimensional perfectionism. Then they rated the attractiveness of potential dating partners. Self-oriented perfectionists found perfectionist dates more attractive. Other-oriented perfectionists found non-perfectionist dates less attractive.